Functionalized zinc(II) dithiocarbamate complexes: Synthesis, spectral and molecular structures of bis(N-cyclopropyl-N-4-methoxybenzyldithiocarbamato-S,S′)zinc(II) and (2,2′-bipyridine)bis(N-cyclopropyl-N-4-methoxybenzyldithiocarbamato-S,S′)zinc(II) - Ethiraj Sathiyaraj; Marimuthu Venkatesh Perumal; Erumaippatty Rajagounder Nagarajan; Chennan Ramalingan (Journal of Saudi Chemical Society, 2018)
Two new zinc and dithiocarbamate integrated metal complexes such as bis(N-cyclopropyl-N-4-methoxybenzyldithiocarbamato-S,S′)zinc(II) (1) and (2,2′-bipyridine)bis(N-cyclopropyl-N-4-methoxybenzyldithiocarbamato-S,S′)zinc(II) (2) have been synthesized and their spectral investigations viz., FT-IR, 1H and 13C NMR as well as single crystal X-ray diffraction studies have been accomplished. Single crystal X-ray analysis of the complex 1 reveals the presence of distorted trigonal bipyramidal and tetrahedral coordination geometry around the zinc. The dithiocarbamate motif acts as bidentate chelating and bidentate bridging ligands between the zinc ions furnishing centrosymmetric dimeric molecules. In the complex 2, the zinc is in a distorted octahedral environment with a ZnS4N2 chromophore. The supramolecular frameworks in the complexes 1 and 2 have been sustained by CH⋯S, CH⋯O and CH⋯π (ZnCS2, and chelate) interactions. Computational studies on complexes 1 and 2 have been executed utilizing DFT-B3LYP/ LANL2DZ method. In both the cases, the HOMO-LUMO calculations imply the occurrence of effective charge transfer within the molecule. Further, the MEP analysis of 1 and 2 implies the negative potential sites are sulfur of NCS2 and oxygen of OCH3 and the positive potential sites are nitrogen of NCS2 in both the complexes along with 2,2′-bipyridine for complex 2. The former sites are susceptible for electrophilic reactions while the latter for nucleophilic reactions. Keywords: Zinc complexes, Dithiocarbamate, X-ray diffraction, Computational study, HOMO-LUMO